Shannin Shamsan COVID-19 Image - Shamsan, Shannin::::::::: (2021)
GIF image of Shannin Shamsan (in the front) and friend Sana Hansoti (in the back) maintaining social distance as required by the Shelter-in-Place order. Shamsan and Hansoti met at Target for errands at the Fremont Hub in Fremont, California.